Managing Ethics in Public Sector: Integrity Approaches - SONGKLIN PRAYOTE (Jurnal Studi Pemerintahan, 2016)
There are two main approaches of ethics, integrity and compliance approach,applying in public administration. In this paper, I would like to study specificallyabout integrity approach, focusing on ethics education and training and ethicalmodels. Methodology used in the study is a documentary research. The findingmight be help public officials in decision-making when they have to encountersome ethical dilemmas in public administration. Integrity and compliance can beperceived as a soft and a hard approach, respectively. An integrity approach usesinternal controls and a compliance approach uses external controls in order tooperate as an ethical organization. The integrity approach is assumed to be moreeffective. This paper has focused on the integrity approach to organizationalethics, therefore describing its orientation and components. Moreover, it clarifiedthe way of implementing this approach within an organization. Ethics educationand training programs, which are embedded in an integrity approach, are cognitive programs in ethical decision-making. Ethical models studying in this paper; Ethics Triangle Model, Ethical Decision-making Model, Ethical Problem solving Model, and Moral Development Model; can be used to help individuals and groups of individuals in organizations to analyze ethical dilemmas they are faced with in daily practice. These models, consequently, are considered as effective means for enhancing decision-making of public officials.